Historical Understanding of Contemporaneity (Russia’s Hawkish War Against Dovish Ukraine) - Bohatyrets, Valentyna (Технодрук, 2022)
Under the scourge of unprovoked russia’s war, collective effervescence is the sense of energy and harmony that we feel together around a shared purpose - to truly embrace the beauty of our backgrounds, culture, and national identity. Furthermore, we want to increase our focus on determining how we in particular have a role to play in driving sustainable Doing Europe practices and raising our awareness of Ukraine’s being European de facto. We work every day to realise the choice made by the Ukrainian people. To make Ukraine a successful, strong, European state, a member of the EU and NATO; Ukrainians take their pride in the country and by joint efforts we will achieve the goal and make Ukraine a success story and move forward. Russian aggression against Ukraine has become a catalyst for many processes that take place in the minds of Ukrainians, first of all, awareness of their main values, virtues and culture. The nation has rallied more than ever, united in defence of the integrity of its country, freedom and independence.
From a new viewpoint from which well-known features reappear, constructing a historical narrative has appeared to be mandatory so that we might find the answers to the most complicated questions regarding the nature or vindication of any historical thinking (Gallie:149). In the context of contemporary geopolitical challenges, history is vital for our understanding of why the unprovoked Russian invasion of Ukraine happened, and embrace the history of Ukrainian national and ethnic identity. As citizens of different countries, different political systems, identity, mentality, cultures and different backgrounds, we have become able to directly understand the cultural ‘otherness’ and determine the relevance of our understanding of what Europe is; what values and standards are the basis of European identity; and what motivates and inspires Europeans to identify with Europe, where the highest social value is a person, and all state and social life is aimed at ensuring maximum comfort and protection of its rights and freedoms, which is the basis for the development of Europe in Ukraine.
Keywords: a historical narrative; ethnicity; Ukraine; Putin’s imperial nationalism; unprovoked russia’s war; freedom and independence